Chemical Profile, Antioxidant, Anti-Inflammatory, and Anti-Cancer Effects of Italian Salvia rosmarinus Spenn. Methanol Leaves Extracts - Matteo Brindisi; Chouaha Bouzidi; Luca Frattaruolo; Monica R. Loizzo; Rosa Tundis; Annabelle Dugay; Brigitte Deguin; Anna Rita Cappello; Maria Stella Cappello (MDPI AG, 2020)
In this study, we evaluated and compared the chemical composition, the antioxidant, anti-inflammatory, and anti-proliferative effects of four methanol extracts (R1-R4), of Salvia rosmarinus Spenn. in two different sites of Southern Italy obtained by maceration or ultrasound-assisted extraction. Extracts of S. rosmarinus collected on the Ionian coast are indicated with the abbreviations R1 (maceration) and R2 (ultrasound-assisted extraction). Extracts of S. rosmarinus collected on the Tyrrhenian coast are indicated with the abbreviations R3 (maceration) and R4 (ultrasound-assisted extraction). The chemical composition was analyzed using High Pressure liquid chromatography-Diod-Array detection-Electrospray ionization-Quadrupole-Mass Spectroscopy (HPLC-DAD-ESI-Q-MS). The antioxidant activity was analyzed by 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) 2,2-diphenyl-1-picrylhydrazyl (DPPH), β-carotene bleaching, and Ferric Reducing Antioxidant Power (FRAP) assays. Antioxidant features were also assessed in lipopolysaccharide (LPS)-stimulated RAW-264.7 murine macrophages, evaluating Reactive Oxygen Species (ROS) production; in the same experimental model, the anti-inflammatory activity of the extracts was investigated. Interestingly, all extracts displayed antioxidant and anti-inflammatory properties. They exhibited significative nitrite production inhibitory activity, whith IC50 values ranging from 3.46 to 5.53 µg/mL, without impairing cell viability. The anti-inflammatory activity was also investigated by Western Blotting and immunofluorescence assay, highlighting the R3 and R4 extracts ability to reduce NF-κB translocation, as well as to disrupt the MAPKs signaling pathway. Extracts exhibited both potential anti-proliferative activity on breast cancer cells, inducing apoptosis, without affecting non-tumorigenic cells, and the ability to inhibit MDA-MB-231 cells' motility. Finally, the rosemary extracts treatment significantly reduced the power of conditioned media, from MCF-7 or MDA-MB-231 cells to induce nitrite production on RAW 264.7 cells, confirming their promising anti-inflammatory activity.